HUBUNGAN STATUS FUNGSIONAL DAN DEPRESI PADA PASIEN STROKE DENGAN PENDEKATAN KONSEP MODEL DOROTHEA E. OREM - Nisfil Mufidah; Rahmad Wahyudi; Sitti Sulaihah; Ach. Baihaki (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Stroke is the leading cause of disability and the second leading cause of death in the world with more than 5.1 million deaths. The result of a preliminary study at the neurology departemant of Anna Medika Hospital Madura reported a high incidence of depression. The purpose of this study is to analyze the relationship between functional status and depression in stroke patients at the Neurology Polyclinic of Anna Medika Madura General Hospital. The Research design using analytics with cross-sectional approach. The independent variable was functional status and the dependent variable was depression. The population of stroke patients was 112 people, the number of samples taken was 87 respondents. The criteria taken were stroke patients in the neurology department of RSU Anna Medika Madura. Simple random sampling technique. Data collection techniques using a questionnaire sheet. Statistical test using Spearman Rank. After the statistical test was carried out Spearman Rank earned value p = 0.010 mean value p = < (0.05) with correlation value = 0.276. which means H0 is rejected. This showed that there was a relationship between functional status and depression in stroke patients at the Neurology Polyclinic of Anna Medika Madura General Hospital.